14
$\begingroup$

Prove that $$p(x,y) = x^4 + y^4 + x^2 + y^2$$ can be written as a sum of squares of three polynomials over $x,y$ for real numbers.

$\endgroup$
  • $\begingroup$ I thought it would be easy.I posed this question to my teacher as well.He was unable to solve it.I was not able to arrive at the answer $\endgroup$ – Sai Krishna Deep Dec 1 '12 at 7:48
  • 1
    $\begingroup$ Actually, I can think of a pretty good reason that some of the coefficients might need to be irrational, square roots of positive whole numbers or possibly fractions. I'm not sure yet, though, I will fiddle with it tomorrow. It is late here. $\endgroup$ – Will Jagy Dec 1 '12 at 7:49
  • 1
    $\begingroup$ Its from a standardized book in India called "Challenge and Thrill of Pre-College mathematics" $\endgroup$ – Sai Krishna Deep Dec 1 '12 at 7:55
  • $\begingroup$ I'm no mathematician, but I can't see how real numbers can suffice. If I take a linear combination of $x^2, y^2, x, y, xy, 1$ and square these, then I get a positive-definite expression for the $x^2y^2$ and $xy$ terms. Therefore it cannot disappear in the reals?! $\endgroup$ – Gerenuk Dec 1 '12 at 9:35
13
$\begingroup$

$(\sqrt{2\sqrt{2}-2}y^2+x)^2 + (-\sqrt{2\sqrt{2}-2}xy + y)^2 + (x^2 + (1-\sqrt{2})y^2)^2 = x^4+y^4+x^2+y^2$.


In fact, there are many other solutions by using brute force, as suggested by Will Jagy in the comments.

Step 1 Let's suppose that $x^4+y^4+x^2+y^2 = \sum_{i=1}^3 (a_i x^2 + b_i xy + c_i y^2 + d_i x + e_i y)^2$. If we write $\vec{a} = (a_1,a_2,a_3)$ and so forth, we obtain the following identities by comparing coefficients:

Part (a): $x^2: \| \vec{d} \|^2 = 1$, $y^2: \| \vec{e} \|^2 = 1$, $xy: \langle \vec{d}, \vec{e} \rangle = 0$.

Part (b): $x^3: \langle \vec{a}, \vec{d} \rangle = 0$, $y^3: \langle \vec{c}, \vec{e} \rangle = 0$, $x^2y: \langle \vec{b}, \vec{d} \rangle = - \langle \vec{a}, \vec{e} \rangle$, $xy^2: \langle \vec{b} ,\vec{e} \rangle = - \langle \vec{c}, \vec{d} \rangle$.

Part (c): $x^4: \| \vec{a} \|^2 = 1$, $y^4: \| \vec{c} \|^2 = 1$, $x^2y^2: \| \vec{b} \|^2 + 2 \langle \vec{a}, \vec{c} \rangle = 0$, $x^3y: \langle \vec{b}, \vec{a} \rangle = 0$, $xy^3: \langle \vec{b}, \vec{c} \rangle = 0$.

(All inner products are standard Euclidean inner products)

Step 2 We consider an orthonormal basis of $\mathbb{R}^3$: $\vec{d}, \vec{e}, \vec{f}$. This used part (a).

Using part (b), we get

$\vec{a} = x_1 \vec{e} + y_1 \vec{f}$,

$\vec{b} = -x_1 \vec{d} - x_2 \vec{e} + y_3 \vec{f}$,

$\vec{c} = x_2 \vec{d} + y_2 \vec{f}$

for some reals $x_1,x_2,y_1,y_2,y_3$.

Step 3 Part (c) tells us that

$x_1^2 + y_1^2 = 1$, $x_2^2 + y_2^2 = 1$. (From norm of $\vec{a}, \vec{c}$ being 1.)

$y_1y_3 = x_1x_2$, $y_2y_3 = x_1x_2$ (From $\vec{b}$ perpendicular to $\vec{a}, \vec{c}$.)

$x_1^2+x_2^2+y_3^2 + 2y_1y_2 = 0$.

In the second equation, if $y_3$ is not 0, then $y_1 = y_2$, which forces $x_1 = x_2 = y_1 = y_2 = y_3 = 0$ in the third equation, contradicting the first equation.

So $y_3 = 0$, which implies $x_1x_2 = 0$. WLOG assume $x_1 = 0$, then $y_1 = \pm 1$. The third equation becomes

$0 = x_2^2 + 2y_1y_2 = 1 - y_2^2 + 2y_1y_2 = 2 - (y_2 - y_1)^2$.

So $y_2 - y_1 = \pm \sqrt{2}$. The first equation tells us that $y_1,y_2$ has norms less than 1, which implies that $y_2 = \pm (1 - \sqrt{2})$. This gives $x_2 = \pm \sqrt{2\sqrt{2} - 2}$.

To summarize, up to symmetry of $(x_1,y_1) \leftrightarrow (x_2,y_2)$, we have $x_1 = 0$, $y_1 = \pm 1$, $y_2 = \pm (1 - \sqrt{2})$ (same sign as $y_1$), $x_2 = \pm \sqrt{2\sqrt{2} - 2}$ and $y_3 = 0$.

Step 4 By picking arbitrary orthonormal basis $\vec{d}, \vec{e}, \vec{f}$, we can substitute the values for $x_1,x_2,y_1,y_2,y_3$ above to get solutions for $\vec{a}, \vec{b}, \vec{c}$. All these would give the required sum of squares decomposition. The decomposition I took above comes from choosing the standard orthonormal basis of $\mathbb{R}^3$.

$\endgroup$
  • 1
    $\begingroup$ Works for me.${}{}$ $\endgroup$ – Will Jagy Dec 1 '12 at 10:21
  • $\begingroup$ I'm not in a position to fully follow this.But thanks for the solution. $\endgroup$ – Sai Krishna Deep Dec 2 '12 at 6:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.